A revised taxonomy of crested newts in the Triturus karelinii group (Amphibia: Caudata: Salamandridae), with the description of a new species - Wielstra, B.; Litvinchuk, S. N.; Naumov, B.; Tzankov, N.; Arntzen, J. W. (Zootaxa, 2013)
We present a taxonomic revision of the crested newt Triturus karelinii sensu lato. Based on the presence of discrete nuclear DNA gene pools, deep genetic divergence of mitochondrial and nuclear DNA, and no indication of gene flow, we interpret this taxon as comprising two species: one covering the southern Caspian Sea shore, the Caucasus and the Crimea, i.e. the eastern part of the total range and another covering northern Asiatic Turkey and western Asiatic Turkey plus the south-eastern Balkan Peninsula, i.e. the central and western part of the total range. We acknowledge that the central/western spe-cies should likely be further subdivided into a central and a western taxon, but we prefer to await a more detailed genetic analysis of the putative contact zone, positioned in northwestern Asiatic Turkey. The name T. karelinii (Strauch, 1870) applies to the eastern species as the type locality is positioned along the coast of the Gulf of Gorgan, Iran. The name T. arntzeni has been applied to the central/western species with Vrtovać, Serbia as the type locality. We show that not T. karelinii sensu lato but T. macedonicus occurs at Vrtovać. Hence, the name T. arntzeni Litvinchuk, Borkin, Džukić and Kalezić, 1999 (in Litvinchuk et al., 1999) is a junior synonym of T. macedonicus (Karaman, 1922) and should not be used for the central/western species. We propose the name T. ivanbureschi sp. nov. for the central/western species and provide a formal species description.